Self-reported health conditions and related driving reduction in older drivers. Issue 4 (2nd October 2018) - Kandasamy, Deepika; Betz, Marian E.; DiGuiseppi, Carolyn; Mielenz, T. J.; Eby, David W.; Molnar, Lisa J.; Hill, Linda; Strogatz, David; Li, Guohua
Abstract: We surveyed self-reported lifetime health conditions (using National Health and Aging Trends Study questions) and related driving reduction in a large multi-site older driver cohort ( n  = 2990) from the AAA Longitudinal Research on Aging Drivers (LongROAD) Study's baseline assessment. Those reporting reduced driving ( n  = 337) largely attributed reduction to musculoskeletal (29%), neurologic (13%), and ophthalmologic (10%) conditions. Women reported health condition-related driving reduction more often than men (14% versus 8%, p <.001). Mobility affects well-being; health professionals should consider that health conditions may cause older adults to reduce driving. Gender differences deserve attention in future research and education efforts.